LOWER EYELID DIROFILARIOSIS: A RARE CASE OF OCULAR PARASITIC INFECTION WITH POSSIBLE ENDEMIC EXPOSURE - Vasović, Dolika; Rašić, Dejan M.; Marjanović, Ivan; Kalezić, Tanja; Lučić, Margita (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Dirofilariosis, caused by the parasitic nematode Dirofilaria repens, is a zoonotic disease with rare ocular manifestations that are being increasingly reported in regions experiencing expanded parasite distribution. Infection in humans manifests as a localized inflammatory reaction and ocular involvement can lead to significant discomfort and diagnostic challenges. While often associated with travel to endemic areas, such as the Mediterranean region, dirofilariosis is also endemic in Serbia, which highlights the possibility of local transmission.Case report: A 38-year-old female patient presented with unusual sensations of movement in her lower eyelid following a vacation in Greece. Clinical examination revealed localized swelling and a palpable moving mass in the lower eyelid. Surgical excision of the lesion was performed, and parasitological analysis confirmed the presence of Dirofilaria spp. Given that dirofilariosis is also endemic in Serbia, the possibility of pre-existing local infection before the patient’s trip cannot be excluded. The patient’s symptoms resolved completely after surgery, with no recurrence or complications noted during follow-up. This case underscores the need for considering parasitic infections in the differential diagnosis of eyelid masses, especially in patients who have recently traveled to or live in endemic areas.Conclusion: This case highlights the clinical presentation and successful management of lower eyelid dirofilariosis, a rare ocular manifestation of Dirofilaria spp. infection. While a travel history to endemic regions can raise suspicion, endemicity in regions like Serbia necessitates factoring in the possibility of local transmission. Early detection and prompt surgical intervention are often curative. Further research is needed to understand local transmission dynamics and the ocular involvement of dirofilariosis in endemic areas, as well as complications that may arise due to inadequate diagnosis and treatment.
Keywords: dirofilariosis; ocular manifestation; eyelid mass; parasitic infection